Respiratory diseases in wood workers. Issue 1 (January 1987) - Carosso, A; Ruffino, C; Bugiani, M
Abstract : A survey was carried out on wood workers and on a group of unexposed, healthy controls. One group of wood workers (group A) were asymptomatic and another (group B) had symptoms either of chronic cough and dyspnoea on exertion (B1) or dyspnoea at work and bronchial hyperreactivity (B2). The control group (group C) was randomly selected from among a population of laboratory workers. No significant differences were found among the groups with respect to the frequency of atopy but the prevalence of a positive skin reaction to wood extracts was significantly higher in the asthmatic subjects. The adjusted FVC and FEV1/FVC% were significantly higher in B1 than in the other groups; the FEV1 was lower in B1 than in B2 and in B2 than in the other groups; TLCO and KCO differed significantly in all four groups. A significant negative correlation was observed between FEV1, MEF50, TLCO and KCO and duration of exposure to wood dusts. The alveolar volumes were not significantly different between the groups and were not correlated with duration of exposure. These results confirm the observation that exposure to wood dust or to some bronchoreactive substances linked with wood working can induce chronic obstructive lung disease (COLD). Some cases of wood dust asthma seem to be related to an immediate allergic reaction, but precipitating antibodies appear to be an index of exposure rather than of disease. The decrease in diffusion capacity can be ascribed to a thickening of the alveolar capillary membranes secondary to an alveolitis like, non-symptomatic, allergic reaction.